Jean-Luc Nancy and La Peau des images: Truth is Skin-deep. (June 2018) - Howells, Christina
This article considers Jean-Luc Nancy's reflections on the nude in painting and photography in the light of his aesthetics, his philosophy of the body and soul, and some of his other writings on portraiture. It explores Nancy's insistence on skin as the truth behind and beyond which no further meaning waits to be revealed: there are no hidden depths, no secret or sacred truths, nothing is concealed beneath the skin.